2018
DOI: 10.1007/s10526-018-09910-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicted ecological niches and environmental resilience of different formulations of the biocontrol yeast Candida sake CPA-1 using the Bioscreen C

Abstract: Environmental resilience of biocontrol microorganisms has been a major bottleneck in the development of effective formulations. Candida sake is an effective biocontrol agent (BCA) against Penicillium expansum, Botrytis cinerea or Rhizopus stolonifer, and different formulations of the BCA have been optimised recently. The objective of this study was to compare the relative tolerance of different dry and liquid formulations of the biocontrol yeast Candida sake CPA-1 to interacting environmental conditions using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Recent studies with different formulations of the BCA Candida sake showed that the three-way interacting CC-related abiotic factors influenced the viability of the yeast cells in different formulations. Thus, some formulations were more resilient than others under such abiotic stress factors [ 78 , 89 ]. Studies with other BCAs such as Clonostachys rosea and non-toxigenic strains of A. flavus for aflatoxin control in maize have also shown that biocontrol efficacy could be reduced or have no effect on the pathogen or toxin production [ 90 ].…”
Section: Biocontrol Strategy Resilience and Adaptation Of A Fungamentioning
confidence: 99%
“…Recent studies with different formulations of the BCA Candida sake showed that the three-way interacting CC-related abiotic factors influenced the viability of the yeast cells in different formulations. Thus, some formulations were more resilient than others under such abiotic stress factors [ 78 , 89 ]. Studies with other BCAs such as Clonostachys rosea and non-toxigenic strains of A. flavus for aflatoxin control in maize have also shown that biocontrol efficacy could be reduced or have no effect on the pathogen or toxin production [ 90 ].…”
Section: Biocontrol Strategy Resilience and Adaptation Of A Fungamentioning
confidence: 99%
“…These methods are also applicable to the search of new isolates as well as on studies of the environment persistence of the antagonist. (Carbó et al, 2018). This type of study was carried out automatically using on equipment as the Bioscreen C that is fast and reproducible.…”
Section: Development Of a Bca-based Productmentioning
confidence: 99%
“…Large amounts of detection and quantification methods have been developed for tracking and es sumamente compleja, y pueden estar presentes otras cepas de la misma especie del BCA aplicado.A pesar de la gran variedad de métodos de detección descritos en la literatura para el estudio de microorganismos en la naturaleza, los que han sido utilizados para monitorizar BCAs, son los métodos directos, microbiológicos y moleculares Carbó et al, 2018)…”
unclassified
“…At the end of the optimization of a biocontrol product, experts should be able to answer many questions about advantages over other products, efficacy, survival under abiotic conditions, or market size . In connection with this, the development process of both film‐forming CPA‐1 formulations was followed stepwise to provide satisfactory answers to these questions …”
Section: Introductionmentioning
confidence: 99%
“…29 In connection with this, the development process of both film-forming CPA-1 formulations was followed stepwise to provide satisfactory answers to these questions. 8,17,19,24,30,31 The present study aimed to verify the potential of two recently developed C. sake CPA-1 formulations using a fluidized-bed spray-drying system, 8 and the specific objectives were as follows: (i) to examine CPA-1 resilience on wine grape berries under controlled conditions of temperature (0, 22, and 30 ∘ C) and relative humidity (RH) (40% and 85%); (ii) to determine the effect of simulated rainfall with different rain intensities and rain volumes on CPA-1 formulations applied to wine grapes; (iii) to evaluate the effect of different periods of cell establishment prior to rain wash; and (iv) to test the efficacy of CPA-1 film-forming formulations to control B. cinerea on the surface of different hosts, such as apples, pears and tomatoes.…”
Section: Introductionmentioning
confidence: 99%